ENVIRONMENTAL RISK MITIGATION ANALYSIS OF GLASS INDUSTRY DEVELOPMENT POLICY ON REMPANG ISLAND - Patminah Nularna; Yustina Yustina (PT. Jurnal Center Indonesia Publisher, 2026)
This research comprehensively analyzes the glass industry development policy on Rempang Island, Batam City, Riau Islands Province, using an environmental risk mitigation approach. Employing a descriptive qualitative method with a case study design and library research, this study examines five main dimensions: the chronology of the Rempang Island case, policy conflicts and controversies, the government regulatory framework, disaster risk analysis from nine environmental perspectives, and overall policy evaluation. The findings reveal that the Rempang Eco City project, designated as a National Strategic Project (PSN) through Permenko for Economic Affairs Number 7 of 2023, triggered prolonged agrarian conflict due to the absence of meaningful participation from indigenous Malay communities who have inhabited 16 ancient villages on the island since 1834. The project implementation was marked by forced evictions, repeated acts of violence, and non-transparent environmental impact assessment (AMDAL) processes. Disaster risk analysis from nine environmental perspectives covering air quality, water quality, coastal and marine ecosystems, sand mining and geological degradation, biodiversity, community health, social-cultural impacts, climate change vulnerability, and environmental governance consistently produces high-risk assessments, affirming that Rempang Island as a small island ecosystem lacks adequate carrying capacity for large-scale glass industrial development without permanent and irreversible ecological damage. Although Presidential Regulation Number 12 of 2025 de facto removed Rempang Eco City from the list of 77 National Strategic Projects under President Prabowo Subianto’s administration, the absence of an explicit revocation of Permenko Number 7 of 2023 creates ongoing legal ambiguity for affected communities. This research concludes that Indonesia urgently requires fundamental reform in its investment-based development policy paradigm, encompassing strengthened indigenous community participation mechanisms, elevation of AMDAL as a non-circumventable legal requirement prior to investment designation, and application of the ecological precautionary principle in small island development.